SOSIALISASI PENGGUNAAN TRACER OUTGUIDE REKAM MEDIS RUMAH SAKIT UMUM PERMATA BUNDA CIAMIS - Ari SUkawan; Feryfadly; Nurmalawati; Taufik Gunawan; Meta Utamii Nuryani (Indonesian Journal of Health Information Management Services, 2022)
One of the activities carried out at the hospital in the medical record section is the processing system in the medical record storage and control section. Management of medical record storage is very important to do in a health care institution because it can facilitate and speed up the rediscovery of medical records stored in storage shelves. Lost medical records, misplaced, misfiles that are difficult to find in a short time become problems that often occur and affect the quality of service. Based on the results of initial observations made with medical records officers at Permata Bunda Ciamis Hospital, it was found that there were still missfiles in the medical record. This activity aims to create a culture of using tracer outguide as a medical record tracking card out of the file storage rack and increasing the knowledge of storage officers. The method used in this socialization is to provide knowledge to the staff in the storage section directly through demonstrations and assistance in the use of tracers in the medical record storage section ending with an evaluation of activities. The results obtained from this activity increase the knowledge of storage officers using a tracer outguide to minimize the occurrence of medical record loss (misfile). Keywords: Medical Record, Tracer, Misfile